(untitled) (Revista LIDER, 2020)
The article makes evident that “conservationism” has a high degree of agreement with the contemporary power structure. It postulates the exposure of how the accumulation mechanism implicit in conservationism becomes evident not only in the economic profitability of its sites, in violation of its published ends, but additionally because –paradoxically– a large number of conservation projects subvert precisely those human relationships with the natural resources that until now have been optimal for their sustainability. For those reasons we shall look more closely at conservationist practices in Chile, taking the implementation of the Tantauco Park as a case study wherein displaced and dispossessed of their ancestral territories